التحليل الوراثي لبعض الصفات الكميّة في عشائر من الفول (Vicia faba L.) - خوري, بولص; معلوف, فؤاد; الأحمد, سمير; غرز الدين, كفاح (Latakia University Journal -Biological Sciences Series, 2017)
أُجريت طريقة الانتخاب المتكرر البسيط Simple Recurrent Selection على نباتات الجيل الثاني لخمس عشائر من الفول المزروع في محطة بحوث تربل (لبنان) التابعة للمركز الدولي للبحوث الزراعية في المناطق الجافة (ايكاردا)، خلال الموسم الأول (صيف 2013)، وتم تقييم الطرز الوراثية المُنتخَبة خلال الموسم الثاني (شتاء 2013-2014)، بهدف تقدير درجة التوريث بالمفهوم الضيق Narrow sense heritability والتقدم الوراثي المتوقع Genetic advance من الانتخاب خلال الأجيال الانعزالية لكلّ من صفات ارتفاع النبات، وعدد القرون على النبات، ووزن المئة بذرة، وغلة النبات الفردي. حقّقت العشيرة S2012-085 أعلى قيمة لدرجة التوريث بين العشائر المدروسة لصفات الغلة البذرية (0.5) ووزن المئة بذرة (0.5) وعدد القرون على النبات (0.5) في حين أخذت العشيرة S2012-133 أعلى قيمة لدرجة التوريث لصفة ارتفاع النبات (0.858). تراوحت قيم التقدم الوراثي المتوقع من الانتخاب لصفة الغلة البذرية من 53% إلى 72.4%، وتميّزت العشيرة S2012-085 بأعلى نسبة للتقدم الوراثي المتوقع بفعل الانتخاب لصفة الغلة البذرية (72.4%). أبدت جميع الصفات المدروسة قيماً متوسطة لدرجة التوريث بالمفهوم الضيق والمترافقة مع نسبة مرتفعة للتقدم الوراثي، ما يبّين أهميّة التباينات الوراثية التراكمية بالنسبة إلى التباينات الوراثية الكليّة، وهذه إشارة واضحة تدل على أهمية تطبيق الانتخاب المتكرر في الأجيال الانعزالية المبكرة والمتوسّطة لتحسين هذه الصفات.Five populations of faba bean were advanced from F2 to F3 generations by simple recurrent selection at Terbol research station, International Centre for Agricultural Research in The Dry Areas (ICARDA), Lebanon. During the growing season summer 2013. The produced genotypes of selection were evaluated in winter 2013-2014 in order to estimate the narrow-sense heritability and genetic advance for seed yield, plant height, pods per plant and 100-seeds weight traits. The results showed that S2012-085 population was superior in heritability for seed yield (0.5), 100-seed weight (0.5) and pods per plant (0.5), while the population S2012-133 was recorded the supreme value for plant height (0.858). The results demonstrate that genetic advance for seed yield trait was varied from 53% to 72.4%, and the highest value of genetic advance for seed yield was belonged to the population S2012-018 (72.4%). Most of traits under research were recorded a moderate values of narrow sense heritability accompanied with high values of genetic advance, indicating to the importance of additive genetic variances related to the total genetic variances, Consequently, recurrent selection is very important to apply in order to improve the traits across segregated generations of faba bean.